Optimising the Quality of Sago Bamboo through Fortification of Cork Fish Flour (Ophiocephalus striatus) with Various Processing Methods - Fattah, Nurlaeli (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was examining several methods of processing snakehead fish with several treatment methods before drying, namely (1) making surimi, (2) making mashed fish, and (3) cooking using an autoclave. Data analysis used a Completely Randomized Design (CRD). The study's results showed that protein levels during the study for all treatments did not significantly affect the protein content of snakehead fish meals. The average protein content was 71.17 ± 1.28 to 88.05 ± 1.28. The highest protein content was obtained in the treatment method for making snakehead fish meals, starting with the manufacture of freshly dried surimi. The Fat ranged from 0.77 ± 0.58 to 1.88 ± 0.58. The lowest fat content was obtained in the treatment of the Making Snakehead Fish Meal processing method by making surimi, then drying at 65o C ± 12 hours. The water content of snakehead fish meal for all treatments was 3.91 ± 1.33 to 6.51 ± 1.31. Carbohydrates for all treatments were, on average, 1.38 ± 0.7 to 2.73 ± 0.7. Protein digestibility is an average of 88 ± 1.7 to 91 ± 1.7. Total Microbes, namely 18,733 ± 1.7 to 8,133 ± 1.7. As for the Organoleptic Test, the treatment that was given the number 9 from the parameters of Appearance, Color, Taste, Aroma, Texture, and Acceptance was the research treatment, namely the production of snakehead fish meal using the method of making surimi first before drying